Quality transformation to improve customer satisfaction: using product, process, system, and behaviour model. (14th June 2023) - Venkatasudhahar, M.; Poornachandrika, V.; Prakash, D. Surrya; Raja, N. Dilip
In recent years automotive manufacturing industries systematically improved their quality parameters principally through strategies within supply chain. However the current performance is not enough, industry dynamics and new technology development require a major quality transformation. Implementation of various quality improvements is the aim of achieving customer delight in many companies. Despite the marked improvements that have come from quality management, quality process, information technology systems, without a transformation within an organisation's culture, quality management will continue to suffer. This paper presents a case study on the application of behaviour model of a quality blue box with a plan, control, assure concept through veto right approach, a process model of robust process automation in customer claim handling, system model of a mature audit tool. This work is carried out in a leading automotive commercial vehicle control system manufacturing company. This case study illustrates to get zero defects by applying behaviour, process, and system models. After implementation, there is a significant change in the reduction of customer claims.